Neurological Deterioration After Mild TBI - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from UMDNJ-New Jersey Medical School, Newark, NJ, studied the cause, course, and outcomes of 757 patients who were admitted over 54 months following mild head injury (MHI) complicated by intracranial hemorrhage (ICH).